Effects of vitamin D supplementation to children diagnosed with pneumonia in Kabul: a randomised controlled trial. (29th September 2015) - Manaseki-Holland, S; Qader, G; Masher, MIM; Bruce, J; Mughal, MZ; Chandramohan, D; Walraven, G
Abstract : Aim: Vitamin D has a role in regulating immune function and deficiency is a risk factor for childhood pneumonia. The authors investigated whether: (1) Supplementation of 100 000 IU of vitamin D3 (cholecalciferol) along with antibiotics reduces the duration of illness in children with pneumonia; (2) vitamin D3 supplementation reduces the risk of repeat episodes. Methods: Design: Double-blind individually randomised placebo-controlled trial. Setting: Outpatient clinics and inpatient department in an inner-city Kabul hospital, Afghanistan. Participants: 453, 1–36 months old children, from an area with known high vitamin D deficiency, clinically diagnosed with non-severe or severe pneumonia (WHO's IMCI diagnostic criteria) at the outpatient clinic from December 2006 to February 2007. Exclusions: Children diagnosed with rickets, other concurrent severe diseases, very severe pneumonia or wheeze. Intervention: Identical-looking syringes with unique identifiers containing vitamin D3 or placebo were randomised and administered orally at diagnosis with regular pneumonia treatment. Follow-up: Daily until signs of pneumonia resolved and then two-weekly for 3 months. Outcome measure: (1) Mean number of days recovery (resolution of IMCI signs of pneumonia) ascertained through daily home-visit or inpatient examinations; (2) incidence of repeat episodes of pneumonia from 14–90 days after the resolution of the index episode ascertained through two-weekly home visits and passive case detection at the outpatients. Results: 224 received vitamin D3 and 229 placebo; randomisation successful with balanced background characteristics in the two arms. Intention to treat survival analysis: (1) No significant difference in the mean number of days to recovery between the vitamin D3 (4.74 days; SD 2.22) and placebo arms (4.98 days; SD 2.89), p=0.17. (2) Risk of a repeat episode of pneumonia within 90 days of supplementation lower in the vitamin D3 (92/204; 45%) compared to the placebo group (122/211; 58%) (RR 0.78; 95% CI 0.64 to 0.94; p=0.01). Vitamin D3 arm went longer without experiencing a repeat episode of pneumonia (mean 72 days vs 59 days; HR 0.71; 95% CI 0.53 to 0.95; p=0.02). Conclusion: A single high-dose oral vitamin D3 supplementation to young children along with antibiotic treatment for pneumonia does not affect length of pneumonia, but reduces the risk of recurrence of pneumonia episodes.